PREVALENCE OF NECROTIZING FASCIITIS DURING RAMADAN AND HAJJ 1427-H - Surahio, Abdul Rashid; Khan, Ashar Ahmad; Farooq, Main Usman; Fatima, Iffat; Azhar, Muhammad Zeeshan (Journal of Ayub Medical College Abbottabad, 2009)
Background: Necrotizing Fasciitis is a rare progressive disease which results in significant rate of mortality and morbidity if there is any delay in diagnosis and treatment. Objectives of this Prospective observational study were to share our experience of dealing necrotizing fasciitis in terms of different presentations, diagnosis, treatment and outcome during Ramadan and Hajj. It was conducted in the Department of General Surgery, Al-Noor Specialist Hospital, Holly Makkah, KSA during Ramadan and Hajj period from 1-8-1427 to 30-1-1428. Methods: Total 35 patients >12 years of age, irrespective of the gender belonging to different nationalities admitted to Al-Noor specialist hospital, Makkah, KSA were included in this study to evaluate the different causative factors, presentations, response to medical/ surgical treatment and outcome. Results: Total 35 patients with male to female ratio of 6:1 were admitted during Ramadan and hajj period from 1-8-1427 to 30-1-1428 (six months) with the features of necrotizing Fasciitis. Out of these 35 patients, 23 (65.7%) were hajji and 12 (34.28%) were residents (Both Saudi and non Saudi) with a ratio of 2:1. Major co-morbid factors were old age, diabetes mellitus, hypertension and renal failure. Among systemic manifestations, 4 (11.42%) developed septic shock and admitted to ICU, 4 (11.42%) needed ventilator support for respiratory failure, and 5 (14.28%) patients developed Myocardial infarction. After resuscitation, 33 patients under went aggressive surgical debridement and two patients died before surgery. Microbiology revealed, 15 (42.85%) Streptococcus Group-A infection, l3 (8.51%) Polymicrobial and 4 (11.42%) MRSA. Diagnosis was conformed by histopathology. Mortality rate was 11.5%. Conclusion: Better outcome in necrotizing fasciitis depends upon early presentation, prompt diagnosis and aggressive surgical debridement. There was strong correlation between severity of necrotizing fasciitis and co morbid factors, general condition at presentation, systemic toxicity and raised WBC count. Keywords: Necrotizing fasciitis, Septic shock, Bullae, Blister